(3eQBI GdCUhd TQM eQbGJ GdhUhds - (3eMeO Hf aQGoeQR Hf Ydj, GdeYQha HedG (B- (3Ch efdG Ch Gdehdi (B- (3NSQh , (B885 (3g` s ((3eMeO Hf eMehOs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj cQe Hfj BOe HGdYbd Gdbhje CeG HYO aEf Chdi eG JbJQMg GdbQGjM GdbhGQM hgh Yde GdCUhd hefg jLJdj YQi GdObGjb GdGLcGejI hbO Ufa ajg GdYdeGA cJHG eYJHQg dG SjeG CUhd GdEeGe aNQ GdESdGe hSejJg eQBI GdCUhd aj TQM eQbGI GdhUhds
(3BNQgG (B:s
(3acPdc GdGLJgGO ajchf GdeLJgO ef dg edcI jbJOQ HgG Ydi GdGSJfHGW cd Mce TQYj aQYi Yf Odjdg adG jfGbj Pdc UOhQ dG COQj ef GdeLJgO ceG SHb s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 328s
(3eYLe GdeDdajf (B3 / 584s
(3cTa GdXfhf (B2 / 1657s
(3TPQGJ GdPgH (B7 / 342s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs